Entropy generation analysis of mixed convective flow in an inclined channel with cavity with Al2O3-water nanofluid in porous medium. (December 2017) - Hussain, S.; Mehmood, K.; Sagheer, M.; Farooq, A.
Abstract: A numerical study has been carried out in the analysis of two dimensional, incompressible and steady mixed convective flow in an inclined channel with cavity. The cavity is filled with Al2 O3 -water nanofluid saturated with porous medium using the Darcy-Brinkman-Forchheimer model. The temperature at the left wall of the cavity is considered as T H and the inlet temperature of the channel is T C while the rest of the walls are thermally insulated. The governing equations are discretized in space using finite element pair Q 2 / P 1 d i s c which leads to the third and second order accuracy in the L 2 -norm for velocity/temperature and pressure, respectively. The discrete system of nonlinear equations is treated by using Newton's method and the associated linear systems are computed using monolithic geometric multigrid solver with Vanka-type smoother. The effects of some physical parameters in the specific ranges such as Richardson number (0.01–20), Reynolds number (10–200), Darcy number (10 −6 –10 −3 ), inclination angle (0°–360°), porosity (0.2–0.8) and solid volume fraction (0–0.04) on the flow are presented. The obtained results are shown in the form of isotherms, streamlines and some other useful plots. It is found that an increase in the inclination angle up to γ = 135°, maximum temperature gradient occurs and the temperature distribution is enhanced in the cavity that results an increase in the heat transfer. For an inclination angle greater than or less than this value, less heat transfer is observed.